Effect of hexamethylenetetramine of Zinc oxide nanowires using chemical bath deposition method - Mohd Aris, Siti Nurnadiah; Azmi, Zaidatul Hanis; Sagadevan, Suresh; Abubakar, Shamsu; Siburian, Rikson; Paiman, Suriati (Wiley, 2023)
In this study, zinc oxide (ZnO) nanowires are grown by chemical bath deposition (CBD) using aqueous solutions with [Zn (NO3)2]: [HMTA] ratios of 1:2/5, 1:1/2, 1:2/3, 1:1, 1:2, and 1:3. The effects of hexamethylenetetramine (HMTA) on the formation of Zinc oxide (ZnO) nanowires are investigated. The XRD results reveal that the dominant peak observed at 2θ = 36.25° indicates preferential growth along the (101) crystal plane, and the ZnO nanowires have a larger crystallite size than the others. The length of the ZnO nanowires, grows with a ZnO seed in the thickness of one and three layers, gets increased from 256.16 ± 15.15 to 497.80 ± 7.84 nm, while the diameter decreases from 497.80 ± 7.84 to 50.34 ± 4.23 nm. The ZnO nanowires deposited by one layer show a similar pattern with the three layers, in which the length is increased from 8.44 ± 0.31 to 14.60 ± 0.51 µm, and the diameter has decreased from 1.95 ± 0.09 to 0.49 ± 0.06 µm. These results support the role of HMTA as a capping agent for the production of ammonia (NH3). This study can control the dimensions of ZnO nanowires using the HMTA concentration to obtain extra-long nanowires desired for piezoelectric applications.